An Analysis of Moral Values in Kamil Kilani’s “Jelifer Fii Bilaadi Al-‘Amaaliqah” and Its Application in Diraasah Natsriyah - Nadal Badi`; Hanik Mahliatussikah; Ibnu Samsul Huda; Nur Anisah Ridwan (Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2020)
This paper aims to (1) investigate moral values in “Jelifer fii bilaadil ’Amaaliqah” and (2) suggest the application of the moral values in the novel to the teaching and learning of dirasah natsriyah.This paper takes a descriptive qualitative approach. Zuchdi’s (1993) content analysis is used for data analysis method. The procedure includes inductive comparison, categorization, tabulation, and making inferences. The data is collected by following Ainin’s (2016) reading and note-taking techniques, which consist of close reading, making manual annotation, describing data, note-taking, and finding linguistic markers reflecting moral values. The result of this paper reveals that the moral values contained in the novel have the following themes: faith in Allah SWT (to have faith, to be grateful, tawakkal, and to pray), positive character traits (curious, responsible, courageous, honest, independent, diligent, wise, disciplined, creative, trustworthy, humble, and indulgent), moral values in social life (caring, communicative, tolerant, polite, democratic, and collaborative). This paper argues that these moral values can be implemented in the lesson plan and syllabus for dirasah natsriyah. Makalah ini bertujuan untuk (1) menyelidiki nilai-nilai moral dalam “Jelifer fii bilaadil 'Amaaliqah” dan (2) menyarankan penerapan nilai-nilai moral dalam novel pada pembelajaran dirasah natsriyah. Makalah ini mengambil pendekatan deskriptif kualitatif. Analisis konten yang dikembangkan oleh Zuchdi (1993) digunakan untuk metode analisis data. Prosedurnya meliputi perbandingan induktif, kategorisasi, tabulasi, dan membuat kesimpulan. Pengumpulan data dilakukan dengan mengikuti teknik membaca dan mencatat yang dikembangkan oleh Ainin (2016), yang terdiri dari bacaan dekat, membuat anotasi manual, mendeskripsikan data, mencatat, dan menemukan penanda linguistik yang mencerminkan nilai-nilai moral. Hasil penelitian ini mengungkapkan bahwa nilai-nilai moral yang terkandung dalam novel memiliki tema-tema sebagai berikut: beriman kepada Allah SWT (beriman, bersyukur, tawakal, dan berdoa), karakter positif (ingin tahu, bertanggung jawab, berani, jujur). , mandiri, rajin, bijaksana, disiplin, kreatif, dapat dipercaya, rendah hati, dan memanjakan), nilai-nilai moral dalam kehidupan sosial (peduli, komunikatif, toleran, sopan, demokratis, dan kolaboratif). Makalah ini berpendapat bahwa nilai-nilai moral tersebut dapat diimplementasikan dalam RPP dan silabus dirasah natsriyah.